0265 Cortisol and C-Reactive Protein Fail to Predict Individual Differences in Neurobehavioral Performance Responses to Total Sleep Deprivation and Psychological Stress. (27th May 2020) - Goel, N; Yamazaki, E M; MacMullen, L E; Ecker, A J
Abstract: Introduction: Individuals show marked differential vulnerability in neurobehavioral deficits from psychosocial stress and sleep deprivation. Although changes in salivary cortisol and C-reactive protein (CRP) typically occur across total sleep deprivation (TSD) and recovery sleep, whether these biological markers during fully rested conditions predict individual differences in cognitive performance during TSD and stress remains unknown. Methods: Thirty-one healthy adults (ages 27–53; mean ± SD, 35.4 ± 7.1y; 14 females) participated in a five-day experiment consisting of two 8h time-in-bed (TIB) baseline nights, followed by 39h TSD, and two 8h-10h TIB recovery nights. A modified Trier Social Stress Test (TSST) was conducted on the day of TSD to induce psychological stress. Salivary cortisol and CRP from blood were obtained at six time points during the study (pre-study, baseline, during TSD, during TSD after the TSST, after recovery, and post-study). A median split of TSD performance [total lapses (>500 ms response time) and errors] on the 10-minute Psychomotor Vigilance Test (PVT) defined cognitively resilient (n=15) and cognitively vulnerable (n=16) groups. Repeated measures ANOVA and post-hoc comparisons corrected for multiple testing, examined cortisol and CRP across time points between groups. Results: In both cognitively resilient and vulnerable individuals, cortisol increased with TSD compared to baseline in the morning and decreased with TSD + psychological stress in the afternoon compared to TSD alone. By contrast, there were no significant changes in CRP levels throughout the experiment. In addition, there were no significant time*group interactions in cortisol or CRP levels. Conclusion: Salivary cortisol increased with TSD compared to baseline and showed a time-of-day effect with stress during TSD. Notably, cortisol and CRP did not differ between cognitively resilient and vulnerable individuals across TSD, psychological stress or recovery sleep and thus are not reliable biomarkers for predicting performance under these conditions. Support: NASA NNX14AN49G.